Runx1t1 (Runt-related transcription factor 1; translocated to, 1) epigenetically regulates the proliferation and nitric oxide production of microglia. - Nimmi Baby; Yali Li; Eng-Ang Ling; Jia Lu; S Thameem Dheen (PLoS ONE, 2014)
Background Microglia, the resident immune cells of the brain, undergo rapid proliferation and produce several proinflammatory molecules and nitric oxide (NO) when activated in neuropathological conditions. Runx1t1 (Runt-related transcription factor 1, translocated to 1) has been implicated in recruiting histone deacetylases (HDACs) for transcriptional repression, thereby regulating cell proliferation. In the present study, Runx1t1 expression was shown to localize in amoeboid microglial cells of the postnatal rat brain, being hardly detectable in ramified microglia of the adult brain. Moreover, a marked expression of Runx1t1was induced and translocated to nuclei in activated microglia in vitro and in vivo. In view of these findings, it was hypothesized that Runx1t1 regulates microglial functions during development and in neuropathological conditions. Methods and findings siRNA-mediated knockdown of Runx1t1 significantly decreased the expression level of cell cycle-related gene, cyclin-dependent kinase 4 (Cdk4) and proliferation index in activated BV2 microglia. It was also shown that HDAC inhibitor (HDACi) treatment mimics the effects of Runx1t1 knockdown on microglial proliferation, confirming that microglial proliferation is associated with Runx1t1 expression and HDACs activity. Further, Runx1t1 and HDACs were shown to promote neurotoxic effect of microglia by repressing expression of LAT2, L-aminoacid transporter-2 (cationic amino acid transporter, y+ system), which normally inhibits NO production. This was confirmed by chromatin immunoprecipitation (ChIP) assay, which revealed that Runx1t1 binds to the promoter region of LAT2 and this binding increased upon microglial activation. However, the enhanced binding of Runx1t1 to the LAT2 promoter could not repress the LAT2 expression when the BV2 microglia cells were treated with HDACi, indicating that Runx1t1 requires HDACs to transcriptionally repress the expression of LAT2. Conclusion/interpretation In conclusion, it is suggested that Runx1t1 controls proliferation and the neurotoxic effect of microglia by epigenetically regulating Cdk4 and LAT2 via its interaction with HDACs.